Comprehensive Evaluation of Durian Quality Based on Principal Component Analysis and Cluster Analysis - Meigu CHEN; Xing'e LIN; Xinguo LI; Xiaodi LIU; Hongmao GAO; Jianhong MING; Minjie DAI; Zhaoxi ZHOU (Shipin gongye ke-ji, 2023)
In order to explore the difference in fruit quality between Hainan domesticated durian variety Zhongre No. 1 and other main commercial varieties, this experiment used the difference significance analysis to compare 10 appearance quality, 5 nutritional quality and 8 mineral quality indexes of 11 durian varieties, and the principal component analysis and fuzzy comprehensive evaluation method were used for comprehensive evaluation. Correlation analysis showed that pulp weight and fruit longitudinal diameter were the most relevant indicators of fruit appearance quality with durian internal quality. Through the PCA of 23 indexes, five principal components were extracted，of which the contribution rates of principal component 1 and principal component 2 were 33.344% and 19.889%, respectively. The "fruit size" (single fruit weight, fruit longitudinal diameter, fruit transverse diameter, pulp weight), K、Zn content in principal component 1, and Mg、Ca content in principal component 2 were the main indicators in durian variety evaluation. The comprehensive scores of durian variety quality indicators were as follows from large to small: Zhongre No. 1, Sultan King, Kang Yaojin, Jianghai, Hulu King, Musang King, Black Thorn, Tomani, Suzaku, D101, and Fire Phoenix. To summarize, Zhongre No.1 and Kang Yaojin had good appearance quality and high contents of K and Zn elements, Jianghai and Sultan King had high contents of Mg and Ca elements, Black Thorn and D101 had good nutritional quality, all of them could be introduced as excellent durian germplasm resources. "Fruit size" and Mg, Ca mineral elements content were the key indexes to evaluate the comprehensive quality of durian, which provided a reference basis for the quality screening and identification of durian varieties.